AN ANALYTICAL PERSPECTIVE OF RESIDENTS’ VIEW ON THE PROVISION OF RECREATIONAL FACILITIES USING WARP-PLS - Wash, Peter Musa; Omar, Shida Irwana; Isa, Mohd Ismail (PLANNING MALAYSIA, 2022)
Recreational facilities are among the vital services that aid in the development of a community, but its provision is complex. Hence, the need for the involvement of residents in the provision processes. This paper aims to examine the residents’ view of the provision of recreational facilities in the Greater Jos metropolis of Nigeria. The data were collected from the field survey and analysed empirically. The partial least squares structural equation modelling technique was applied in analysing the responses. The results show that the provision has a significant positive effect on the relationship between appropriateness and stakeholders' involvement. In contrast, the provision had a significant negative effect on the relationship between accessibility indicators. Accessibility does not affect the relationship with the provision of recreational facilities. In conclusion, it has been determined that the relationship between the provision is stronger with the appropriateness in terms of categories and attractiveness of the facilities.